Circumventing rent controls with tenants’ maintenance fees: Evidence from Korea - Yun, Sungjin; Choi, Hoon (Journal of housing economics, 2025)
•This paper examines the use of side payments to circumvent rent control policies.•Maintenance fees significantly increased following the expansion of rent control.•This increase is evident in units not subject to strict maintenance fee regulations.•Landlords may target individuals perceived as having weaker negotiating power. This paper investigates the use of side payments to circumvent rent control policies, focusing on the 2020 amendment to Korea's Housing Lease Protection Act. Using a difference-in-differences-in-differences approach with data from the 2019–2022 waves of the Household Income and Expenditure Survey, we find a significant increase in maintenance fees following the expansion of rent control. This increase is particularly evident in units not subject to strict maintenance fee regulations, suggesting that landlords exploit regulatory gaps by raising fees in response to the rent cap. Our findings further indicate that individuals disproportionately affected by higher maintenance fees tend to be female, aged 30 to 39, aged 70 or older, and lacking a college degree. This pattern suggests that landlords may target individuals perceived as having weaker negotiating power, thus capitalizing on potential vulnerabilities.